2021
DOI: 10.1021/acs.langmuir.1c00559
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Competitive Adsorption of Hydrophilic Nanoparticles and Oil-Soluble Surfactants at the Oil–Water Interface

Abstract: Fundamental insights into the interplay and self-assembly of nanoparticles and surface-active agents at the liquid−liquid interface play a pivotal role in understanding the ubiquitous colloidal systems present in our natural surroundings, including foods and aquatic life, and in the industry for emulsion stabilization, drug delivery, or enhanced oil recovery. Moreover, wellcontrolled model systems for mixed interfacial adsorption of nanoparticles and surfactants allow unprecedented insights into nonideal or co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…In this system, Φ of surfactants is 71.3% (Table ). Because D s at this condition is comparable to that at a pristine interface, it is proposed that the number of surfactants in the vicinity of a nanoparticle is small due to a repulsive interaction between the nanoparticle and surfactant . By considering the types of interactions that may be relevant for the system involving nanoparticles and surfactants at a nonaqueous liquid interface, we found that the repulsion was phenomenologically consistent with Coulombic effects in nonaqueous solutions. , …”
Section: Resultsmentioning
confidence: 53%
“…In this system, Φ of surfactants is 71.3% (Table ). Because D s at this condition is comparable to that at a pristine interface, it is proposed that the number of surfactants in the vicinity of a nanoparticle is small due to a repulsive interaction between the nanoparticle and surfactant . By considering the types of interactions that may be relevant for the system involving nanoparticles and surfactants at a nonaqueous liquid interface, we found that the repulsion was phenomenologically consistent with Coulombic effects in nonaqueous solutions. , …”
Section: Resultsmentioning
confidence: 53%
“…The synchrotron reflectivity measurements (XRR) at the decane-water interface were performed at the Liquid Interface Scattering Apparatus (LISA) diffractometer at the P08 beamline, PETRA III for its delivery of X-rays with high brilliance (DESY, Hamburg, Germany) [47,48] and are described in detail in our recent publication [49]. Briefly, a 25 keV collimated X-ray beam with a size of 0.05 x 0.4 mm (vertical x horizontal direction) probes the gas/liquid surface and liquid/fluid interface while varying the incident angles (α i ), without moving the sample, to obtain a reflectivity profile as a function of the momentum transfer q = 4πsin(α i )/λ, where λ = 0.496 Å.…”
Section: X-ray Reflectivity 214a Experimentalmentioning
confidence: 99%
“…The NPs self-assemble at a quiescent air/water surface and oil/water interface, with an immersion depth that can be determined in situ from high-resolution X-ray reflectivity (XRR) data. This discussion is based on a dataset and analytical approach that was also used in our recent publication which focuses on an in-depth discussion of particle assembly at the oil/water interface in presence of oil-soluble surfactants [49]. The purity of the particle dispersions (0.1 w/w% at aqueous pH ~ 5.8) and decane are tested with time-resolved interfacial tension measurements before the XRR tests (Supplementary Section S3, Fig.…”
Section: In-situ Observation Of Self-assembled Nanoparticles At Liqui...mentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 nanoparticles could effectively improve surfactant-enhanced oil recovery [ 13 ]. Furthermore, the use of surfactants in heavy oil recovery has also shown advantages [ 14 , 15 ]. However, there are few studies on the possible synergistic effect of using both nanofluids and surfactants in heavy oil recovery, and the mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%